التنفيذ العيني لإللتزام في القانون المدني الجزائري - سراح شهر زاد (المسيلة, 2023)
إن االلتزامات في عممية تنفيذىا تتطمب أن تنفذ عينا وىو األصل، أي أن يقوم المدين بتنفيذ ذات ما التزم بو والمتفق عميو في العقد. ومن شروط تحقيق التنفيذ العيني ليذا االلتزام البد أن يكون ىذا التنفيذ ممكنا أضافة الى ذلك أال يكون مرىقا المدين وعمى الدائن إعذاره واال يكون فيو مساسا بالحرية الشخصية المدين، والتنفيذ العيني لاللتزام يكون إما قيام المدين بعمل أو لالمتناع عنو أو بإعطاء شيء أما بخصوص ضمانات حق الدائن تتمثل في الدعوى المباشرة وغير المباشرة والبوليصة وأخرى الدعوى الصورية وأخيرا الحق في الحبس. ولتنفيذ ىذا االلتزام أورد المشرع الجزائري نصوصا قانونية تنص عل وسائل التنفيذ العيني لاللتزام فيناك ماىي مباشرة وأخرى غير مباشرة كالغرامة التيديدية. Summary The obligations in the process of their implementation require that they be implemented in kind, which is the principle, that is, that the debtor performs the same commitments and agreed upon in the contract. Among the conditions for realizing the specific implementation of this obligation is that this implementation must be possible in addition to that it should not be burdensome to the debtor and the creditor must notify him and that it should not affect the personal freedom of the debtor. It consists of the direct and indirect lawsuit, the policy, the moot lawsuit, and finally the right to imprisonment. In order to implement this obligation, the Algerian legislator provided legal texts stipulating the means of real implementation of the obligation. There are direct and indirect ones, such as a threatening fine.
Keywords: التنفيذ العيني لإللتزام - القانون المدني الجزائري